Decodificando aspectos psicosociales e ideológicos en la búsqueda de la verdad objetiva y la verdad jurídica - Montero López, Víctor (2020)
Documentary and content analysis of various legal and epistemological texts was carried out in order to capture the differences between objective truth and legal truth, decoding psychosocial and ideological aspects behind them. Useful analyzes in psychology in the clinical, legal, social, etc. areas.